2005
DOI: 10.1152/jn.00926.2004
|View full text |Cite
|
Sign up to set email alerts
|

Superior Colliculus Neurons Use Distinct Operational Modes in the Integration of Multisensory Stimuli

Abstract: Many neurons in the superior colliculus (SC) integrate sensory information from multiple modalities, giving rise to significant response enhancements. Although enhanced multisensory responses have been shown to depend on the spatial and temporal relationships of the stimuli as well as on their relative effectiveness, these factors alone do not appear sufficient to account for the substantial heterogeneity in the magnitude of the multisensory products that have been observed. Toward this end, the present experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
142
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(158 citation statements)
references
References 45 publications
15
142
1
Order By: Relevance
“…That is, the response to auditory-tactile stimuli was greater than the response to auditory or tactile stimuli in isolation, but was not greater than the summed response to auditory and tactile unisensory stimuli (Stein and Meredith, 1993). Previous fMRI studies of auditory-visual integration in STS (Beauchamp et al, 2004a;Beauchamp et al, 2004b;Hein et al, 2007;Van Atteveldt et al, 2004;van Atteveldt et al, 2007) and auditory-tactile integration in auditory cortex (Kayser et al, 2005) have also not observed super-additive changes in the BOLD signal, perhaps because only a few single neurons show super-additivity (Laurienti et al, 2005;Perrault et al, 2005). Supporting this idea, in single-unit recording studies, only a small fraction of STP neurons respond to both auditory and tactile stimulation (Bruce et al, 1981;Hikosaka et al, 1988); the same is true in multisensory regions of cat cortex (Clemo et al, 2007).…”
Section: Multisensory Integration In Stsmsmentioning
confidence: 83%
“…That is, the response to auditory-tactile stimuli was greater than the response to auditory or tactile stimuli in isolation, but was not greater than the summed response to auditory and tactile unisensory stimuli (Stein and Meredith, 1993). Previous fMRI studies of auditory-visual integration in STS (Beauchamp et al, 2004a;Beauchamp et al, 2004b;Hein et al, 2007;Van Atteveldt et al, 2004;van Atteveldt et al, 2007) and auditory-tactile integration in auditory cortex (Kayser et al, 2005) have also not observed super-additive changes in the BOLD signal, perhaps because only a few single neurons show super-additivity (Laurienti et al, 2005;Perrault et al, 2005). Supporting this idea, in single-unit recording studies, only a small fraction of STP neurons respond to both auditory and tactile stimulation (Bruce et al, 1981;Hikosaka et al, 1988); the same is true in multisensory regions of cat cortex (Clemo et al, 2007).…”
Section: Multisensory Integration In Stsmsmentioning
confidence: 83%
“…Furthermore, progressive increases in auditory stimulus intensity resulted in concomitant response changes, which is also a common response feature observable in many auditory cortices. In fact, numerous parametric studies of stimulus feature processing have been conducted in each of the sensory systems, as well as for bimodal multisensory neurons (Meredith and Stein, 1986;Perrault et al, 2005). These investigations showed that multisensory neurons directly alter their discharge rates in relation to systematic increases (or decreases) in stimulus effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A rough determination of threshold and saturation was first made, and one additional, stimulus intensity was chosen to span these extremes (see also Perrault et al, 2005 andStanford et al, 2005;Alvarado et al, 2007a;2007b). Once determined, these same stimulus parameters (effectiveness and duration) were used for individual modality-specific and combined stimuli.…”
Section: General Testing Paradigmmentioning
confidence: 99%
“…visual, auditory, and somatosensory), and the ability of its neurons to integrate the information derived from cross-modal events. Consequently, concordant cross-modal stimuli evoke SC responses that can be well above those elicited by their individual component stimuli (e.g., Meredith and Stein 1983;Wallace et al, 1998;Jiang et al, 2001;Calvert et al, 2004;Perrault et al, 2005;Stanford et al, 2005). Multisensory response enhancement in single neurons in the cat SC depends mostly on the synergistic interaction of unisensory descending influences from the anterior ectosylvian cortex (AES) (Wallace and Stein 1994;Wilkinson et al, 1996;Jiang, et al, 2001Jiang, et al, , 2002Stein 2005;Stein and Stanford 2008).…”
Section: Introductionmentioning
confidence: 99%